Comparison of the Combined Effects of Hip and Knee Muscle Strengthening vs. Knee Muscle Strengthening Alone on Pain, Function and Gait Parameters in Knee Osteoarthritis - Paul, A. K.; Anwer, S.; Rau, S. S.; Alghadir, A. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2016)
Objective: This randomized controlled study aimed to find out the combined effects of hip and knee muscle strengthening vs. knee muscle strengthening alone on pain, function and gait in knee osteoarthritis.Methods: Individuals with unilateral knee osteoarthritis (n=40; male, 18; female, 22) were randomized to participate hip and knee muscle strengthening exercise (n=20; mean age, 53.1 years) or knee muscle strengthening exercise (controls, n=20; mean age, 54.2 years). Participants were randomized to receive 18 sessions (45-min sessions a day/3 days/week for 6 weeks) of either hip and knee muscle strengthening exercises or knee muscle strengthening exercise alone. The numeric rating scale (NRS) and reduced Western Ontario and McMaster Universities Osteoarthritis (WOMAC) index were used to measure the pain intensity and knee function, respectively. Gait parameters were measured using the computer dynography (CDG).Results: The hip and knee muscle strengthening exercise group has shown a significantly greater reduction of pain and improvement of knee function as compared to the knee muscle strengthening exercise group (p<0.05). Similarly, the hip and knee muscle strengthening exercise group has shown significant improvements in gait parameters as compared to the knee muscle strengthening exercise group (p<0.05).Conclusion: This study concluded that the addition of hip muscle strengthening along with knee muscle strengthening reduces pain and improves function, and gait parameters in individuals with knee OA.
Keywords: rehabilitation; osteoarthritis; pain; function; gait; strength